ANALISIS KEBIJAKAN PENGELOLAAN SAMPAH PERKOTAAN DI KOTA MALANG - Khoiron, Khoiron (IKESMA, 2010)
Solid waste is important issue in urban area that is faced continously in line with increase number of residents and improvement of development activity. Every day 2-3 litres of solid waste is produced by everyone in urban area. Solid waste could cause environmental pollution and a threat to human health The purpose of this research isÂ  describing and analyzing policy of local government in management of municipal waste wich comprised by; organization, accomplishment of infrastructures and human resources, regulations, programs and analyze barrier factors in implementation municipal waste management policy. This research is descriptive research by using qualitative method, during four months (September â December 2007) in region Malang City. The result of this research is the organization which manage municipal solid waste has operated concordant with regulations. Limited quantity and quality of human resources,Â  infrastructures (dust bin, transfer of depo, truck conveyor, heavy equipment and landfill area). Has not regulation about municipal solid waste management comprehensively. The main barrier factors of implementation municipal solid waste management are limited budget, limited infrastructure, low of awareness and participation of resident. Â  Keywords : policy analysis, municipal solid waste, management